Incorporating Research in Chemistry Courses: Research Data-Based Learning - Fatimah, Is; Khoirul Anas, Argo (International Journal of Engineering and Technology, 2018)
Kinetic Chemistry and Catalysis Chemistry courses were conducted. Aim of the project is to evaluate the effectivity of the model in improving student learning outcome in both courses which are included in the physical chemistry scheme. The courses are getting important attention in difficultness level since those are topics with the abstract and mathematically delivered. In the program students have some individual and group tasks based on research data-simulations to be finished until pass the such level for the completion standard learning outcome and for brief application of the topics in both lecturers visiting professor lectures were given. The teaching model was evaluated based on the difficultness level of each topic and also the percentage of student passing learning outcomes. The results showed that the model was sufficiently give positive impacts. In this project, a teaching-learning model of research data-based learning (RDBL) model for to the students and teaching learning process since more than 80 % were successfully passed the standard. The program was recommended for other courses.